STUDYING LITERARY PRONUNCIATION IN TEACHING SYNTAX - Sevda Abbasova (European Research Materials, 2024)
Acquiring the norms of literary pronunciation ensures students' mastery of the language, the realization of the standards of the Azerbaijani language, and in general, the improvement of the quality of education. That is why students' acquisition of literary pronunciation habits is considered one of the most important tasks facing the teaching of the Azerbaijani language. In each Azerbaijani language lesson, appropriate lexical work on the text is carried out, tasks on literary pronunciation and orthography are solved. In Azerbaijani language classes, there are opportunities for mastering literary pronunciation habits in the work process for each content line (listening, reading, writing, language rules). Azerbaijani language classes in primary education have wide opportunities to form reading habits. Thus, in current textbooks, each learning material begins with a connected text and serves the purpose of realizing the standards of listening comprehension and speaking, as well as reading content lines. According to the modern educational thought, the lesson should start with the reading of the related text and end with the narration of that text. Each of these is possible with pronunciation. The issues mentioned in the article are analyzed and summarized and relevant proposals are put forward.